The Comparative Study of Obesity among Mothers with Different Ethnic Groups in Northern IRAN - GR Veghari; AR Mansourian (Tehran University of Medical Sciences, 2007)
"nBackground: To evaluate the prevalence of obesity and some related factors in the villages around Gorgan which is a multi-racial and capital city of Golestan Province, northern Iran. "nMethods: This was a cross-sectional study with 2854 women participated. Interviewers recorded the data using the questionnaire. Subjects were weighed on scales and had their height, waist, and hip circumferences. Economic status was categorized based on 10 consumer items considered necessary for modern-day life (Low >=3, Moderate = 4-6 and Good= 7-10). Three ethnic groups were compared in this study: Fars (native), Turkman and Sistani. This study carried out in rural area of Golestan Province in 2004."nResults: Body Mass Index (BMI) in ranges of (25-29.9), (30-39.9) and (>=40) was observed in 28.3%, 15.9% and 0.5% of the subject, respectively. The frequency of BMI over 25 among Fars(native), Turkman and Sistani mothers was 64.3%, 43.4% and 32.9%, respectively and statistical differences was significant (P< 0.02). In 39.1% of these women, the Waist to Hip Ratio (WHR) exceeded 0.8 and the index was higher in Turkman women compared with other groups. The frequency of economic status was 34.7%, 50.8% and 55.9%, respectively, without any significant difference. The prevalence of obesity in literate women was significantly higher than in illiterate women (P< 0.04)."nConclusion: Obesity is a common health problem among women in the rural areas of Gorgan and this abnormality is varied among three different ethnic groups in this region.